Halal Tourism Destination Revitalization Strategy in the Tretes Ecotourism ‘Plezier’ Area - Khakim, Akhmad; Hakim, Luchman; Putra, Fadillah; Prawoto, Sigit (Graduate School, Universitas Brawijaya, 2022)
The Tretes Ecotourism area has been a plezier tourist destination since the Dutch colonial era, which offered mountainous natural charm, the weather that urban people desire, strong community culture, and the strategic position of the city center that had not shown the number of visits it should have. Especially if it is compared to Batu Tourism City, which is located further from Surabaya. Several problems were still unresolved, such as the availability of tourism diversity infrastructure and services. Moreover, the stigma of a location for hidden prostitution was a serious problem that can reduce tourist confidence. Using Butler's Tourism Area Life Cycle (TALC) theory about the development phases of tourism destination areas, this paper offered three revitalization strategies to return the Tretes Tourism Area as a favorite tourist destination. First, the Optimization Strategy, namely optimizing the potential possessed; Second, the Response Strategy, namely overcoming the crucial and urgent problems that are felt by tourists when visiting Tretes; Third, the Connection Strategy, which was to connect potential with market needs (link and match), services and tourism trends at the domestic and foreign levels. Developing Halal Tourism (Halal Tourism), which was becoming an international tourism trend, was expected to be an exit strategy for various tourism problems in Tretes by optimizing the potential for environmental tourism (Ecotourism) so that it became an alternative destination for the educational tourism market and family tourism in Indonesia. Keywords: Ecotourism, Halal Tourism, Tretes.